POLIGAMI DALAM KAJIAN HUKUM ISLAM (Studi Analisis Pandangan Hasbi Ash-Shiddieqy) - Mahridha, Mahridha (State of Islamic Institute Langsa, 2017)
Nowadays, the phenomenon of polygamy has become a social phenomenon in marriage which is much talkedabout and controversial. On the one hand polygamy is rejected with various arguments, both normative, psychological and even highly touched with gender inequality. On the other hand polygamy is promoted because it is considered to have a firm normative background and is seen as an alternative in solving social problems that arise in society. Controvercy araised due to the concept of justice to wives in polygamy tends to be understood in terms of quantitative. The article tries to discuss Hasbi Ash-Siddieqy?s opinion about polygamy and how the method of judgement extraction used by Hasbi Ashiddieqy about polygamy. According to Muhammad Hasbi Ash-Shiddieqy polygamy is not allowed, because justice in terms of love and affection is very difficult to be realized. The method of judgement extraction used by Hasbi Ash-Shiddieqy related to his opinion is the method of Mashlahah al-Murshalah, which is done by analyzing Al-Qur'an An-Nisa 'verse 3 and the relation of that verse with verse 129 and hadith which is narrated by Imam Ahmad. He takes an account on it?s mashlahat and mafsadat and the possibility of the realization of justice in terms of love and affection in the polygamy family.